Síntesis de un termoplástico de almidón de cáscara de yuca (maniot sculenta) influencia del uso de látex de caucho, glicerina y agua en su resistencia mecánica y absorción de agua - Dávila Marín, Diana Lucía (2019)
In the present work, the influence of plasticizer concentrations: water, glycerin and latex is evaluated, maintaining a fixed amount of acetic acid and cassava shell starch in the preparation of a biopolymer. By using concentrations of glycerin, acetic acid, water and rubber latex together with cassava husk starch it is possible to obtain a biopolymer at a temperature of 69 ° C, there were 27 tests in total. Each of the samples obtained was analyzed to determine its resistance to understanding, water absorption, density, penetration, mold adoption and humidity. At the end of this research study, the methodology for the preparation of a cassava starch biopolymer was determined. According to the statistical analysis, the TPS25 with a composition of 14.96% starch, 0.24% acetic acid, 4% glycerin, 79.8% water and 1% natural banana latex, has better mechanical properties and resistance, presenting a density of 5.90 gr / cm3, 0.0 mm penetration and 4.33 water absorption index